Six new Taraxacum (sect. Taraxacum) species (Asteraceae) from Finland and Sweden - Räsänen, Juhani (Memoranda Societatis pro Fauna et Flora Fennica, 2013)
Six new species of Taraxacum sect. Taraxacum from Finland are described here based on both field studies and cultivated material. Their morphology is compared with closely related species, and a survey of their known distribution is given. Holotypes are deposited to H. T. cabannaeforme have been found at many locations in southern Finland, but the number of plants is usually small. T. coartatiforme is locally common in Joensuu, North Karelia; elsewhere it is very rare. T. ossiclivosum is distributed from eastern Finland to South Savo, being more common in the latter. Although T. sinus-avis is evident especially in North Karelia, occurrences in southern Finland and Sweden indicate that the distribution area may be quite extensive. T. subinvestiens ja T. volitans are known only to exist in Joensuu, North Karelia. Additional studies are required to clarify their total distributions.